The correlation between breath acetone and blood betahydroxybutyrate in individuals with type 1 diabetes. (28th October 2020) - Hancock, Gus; Sharma, Shrinivas; Galpin, Martin; Lunn, Daniel; Megson, Clare; Peverall, Rob; Richmond, Graham; Ritchie, Grant A D; Owen, Katharine R
Abstract: Ketone testing is an important element of the self-management of illness in type 1 diabetes. The aim of the present study was to see if a breath test for acetone could be used to predict quantitatively the levels of the ketone betahydroxybutyrate in the blood of those with type 1 diabetes, and thus be used as an alternative to capillary testing for ketones. Simultaneous capillary ketones and breath acetone were measured in 72 individuals with type 1 diabetes attending a diabetes clinic and on 9 individuals admitted to hospital with diabetic ketoacidosis. Capillary blood measurements ranged from 0.1 mmol l −1 (the lower limit of the ketone monitor) to over 7 mmol l −1, with breath acetone varying between 0.25 and 474 parts per million by volume. The two variables were found to be correlated and allowed modelling to be carried out which separated breath acetone levels into three categories corresponding to normal, elevated and 'at risk' levels of blood ketones. The results on this limited set of participants suggest that a breath acetone test could be a simple, non-invasive substitute for capillary ketone measurement in type 1 diabetes.